Performance of Quantitative and Qualitative Traits and their Genetic Analysis in Bamboo Species at Tarai Region of Pantnagar, Uttarakhand - Bhandari, M. S.; Kaushal, R.; Tewari, S. K. (Indian Forester, 2016)
Fourteen species of bamboos were evaluated for coefficient of variation, heritability and genetic advance estimation. Analysis of variance revealed adequate genetic variability among species for most of the characters studied over the years. Based on pooled analysis, heritability estimated were high and coupled with high to moderate genetic advance for biomass, inter-nodal length, dry matter digestibility, crude fibre, crude protein content and dry matter percentage indicating predominance of additive gene effects for these characters.